Cardiac masses and the role of imaging in their diagnostic - Roungos Alexandros E.; Zăvoi Alexandra; Leonte Andreea; Bostan Mădălina M.; Dabija Anca; Bitere Eugen; Sascău Radu A.; Stătescu Cristian (Sciendo, 2023)
Myxomas are the most common primary tumors of the adult heart and should be considered in the differential diagnosis of intracavitary cardiac masses, along with thrombi and vegetations.